Production of membrane for co₂/n₂separation effect of diluents extraction time on pp-dpe membrane - Ahmad Fadhil Hanafi, Abdullah (2014)
The main factors that contribute for the raising of global warming are CO₂ gas. Production of membrane is actually one of the methods for the separation of CO₂ gas. Membrane technology is continuity and simplicity process compared to the others conventional separation technology. The membranes were prepared from thermal induced phase separation method with 80 wt% of diphenyl ether using the hot steel as a casting with thickness of 500 μm. The membranes were selected to extract into the methanol within 1 hour, 2 hours, 3 hours, and 4 hours of immersion. For the physical and chemical characterization membrane, Scanning Electron Microscopy (SEM) and Fourier Transform Radiation (FTIR) will be used. This research need to calculate the gas permeability and selectivity after single gas permeation is tested with different of pressure. Refer to SEM analysis, the figure for the 4 hours time diluents extraction gives the better pore production compare to 3 hours, 2 hours and 1 hour diluents extraction as the methanol completely remove all the air inside the membrane. If the methanol completely removed the air inside the membrane, the image capture becomes clear and better pore will produced. For FTIR analysis, there have no different functional group inside the membrane after immersed into the methanol. From 1 hour until 4 hours of diluents extraction of membrane have the same functional group of alcohol with the structure of (O-H) stretch that mean the presence of methanol inside the membrane and functional group of ether (C-O-C) stretch and alkanes (C-H) stretch since the membrane is produced by polypropylene and diphenyl ether as a solvent. For the gas permeation, the diluents extraction into methanol for 4 hours gives the highest permeability for the CO₂ and N₂ single gas permeation test. The relation between gas permeation tests with SEM morphology test for the better pore on cross section membrane will cause the good permeability on CO₂/N₂ gas. However, it is difficult to ensure the selectivity of the membrane increase when the permeability increase since the permeability is inversely proportional to selectivity